Case report: A case of high grade serous carcinoma of peritoneal origin - Liu, Yiming; Wang, Sixian; Wu, Yingchao; Chen, Guowei; Zhang, Junling; Wang, Xin (Frontiers in Oncology, 2024)
This case report describes an 80-year-old female patient admitted to the emergency department due to abdominal distension, abdominal pain, and hematemesis persisting for three days. Subsequent postoperative pathological examination confirmed the diagnosis of peritoneal cancer. The occurrence, diagnosis, treatment, and prognosis of primary peritoneal cancer (PPC) are presented in detail. PPC is a type of cancer originating from the primary peritoneal mesothelium organization, causing diffuse malignant tumors in the abdominal and pelvic regions. Due to the lack of specific clinical manifestations for this disease, the importance of early diagnosis and treatment is hereby emphasized. The article also mentions the histological source of this type of cancer and the advantages of preoperative intraperitoneal chemotherapy in improving the efficacy of PPC treatment. Finally, the importance of a comprehensive treatment approach and proficient use of targeted therapy techniques are highlighted to enhance the treatment outcomes of PPC.